Gender and Public Policies - Farah, Marta Ferreira Santos (Revista Estudos Feministas, 2004)
The paper consists on an analysis of the incorporation of the gender perspective by public policies at the subnational level of government in Brazil. The article begins with a reconstitution of the gender agenda and its relations with the State reform agenda and the public policies reform agenda, since the 80s. Taking as reference the proposals that came from the women movement and from feminist entities, the article analyses programs from three sectors – health, violence against women and employment and income generation. The analysis focuses on the adherence of these programs to the gender agenda.